Effect of season on the biochemical characters of native buck semen ( Capra hireus) - SRINIVAS, M; NAIDU, K VENUGOPAL; CHETTY, A VENKATAMUNI (The Indian Journal of Animal Reproduction, 2002)
Evaluation of various semen characteristics using MBRT, RRT-I RRT-11 and pH was conducted during winter and summer. HTVT, Cold Shock and R-value were significantly higher during winter than summer. The quality of semen Willi found to be superior in winter than summer season.